ANALISIS UKURAN DAN TIPE STOMATA TANAMAN DI ARBORETUM SYLVA INDONESIA PC UNTAN PONTIANAK - Utami, Rati; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to measure the size and to determin stomata types from  34 plants in Arboretum Sylva Indonesia PC Untan Pontianak. This research used laboratory descriptive method. The stomata length and  width were measured using macrometer. Stomatal types were grouped according to the arrangement of epidermal cells adjacent to the guard cells. The length size was categorized to be less long, long, and very long of which five sp, six sp, 23 sp subsequenly. The width  was categorized to be less wide, wide, and very wide. Category less width and width were the same as 17 sp. However  very wide category was not found. There were five stomata types found in the Arboretum Sylva Indonesia PC Untan Pontianak namely parasitic, anomocytic, anisocytic, aktinositik and siklositik, of which were 21 sp, four sp, five sp, two sp, and two sp, subsequently. The parasitic type was the most common type. Keywords: Stomata Size and Type, Arboretum Sylva Untan.